WANPRESTASI PEMBORONG (CV. BERKA) DALAM PERJANJIAN KERJA DI KELURAHAN SEI BANGKONG KECAMATAN PONTIANAK KOTA - MITHA NOVIA INDRIANTI NIM. A1012171056 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract The work agreement in repairing the construction of the ground floor of the house between CV. Berka with the owner of the house creates a legal relationship that regulates the rights and obligations of each party, which must be realized in a work agreement to repair the construction of the ground floor of the house in oral form and has been agreed upon by both parties. But in reality the CV. Berka did not carry out his achievements in carrying out repairs to the construction of the ground floor of the house properly, namely the occurrence of time delays in the process, which initially the house repair work must be completed within 2 weeks from the start date of carrying out repairs on September 6, 2021 and is expected to be completed on September 19, 2021 is in accordance with the agreement, but in reality the process exceeds the specified time so that it does not provide maximum results for the home owner.The formulation of the problem: